Exploring the prospects for adaptive governance in marine transboundary conservation in East Africa - and Tuda, Arthur Omondi; Kark, Salit; Newton, Alice (Marine Policy, 2019)
This article explores the prospects for adaptive governance in a proposed marine transboundary conservation initiative in East Africa. Adaptive governance that involves interdependent state and non-state actors learning and taking action on joint environmental problems is suggested for effective transboundary resource governance. Using the concept of adaptive co-management, the current multi-stakeholder marine governance systems in southern Kenya and northern Tanzania are compared to illuminate opportunities and constraints for adaptive marine transboundary conservation governance between Kenya and Tanzania. The concept of networks and the formal method of social network analysis (SNA) are applied as the main methodological device. Using questionnaire and semi-structured interviews, social network data of 70 organizations (local resources users, government agencies and NGOs) was generated from Kenya (n = 33) and Tanzania (n = 37). Results show the existence of strong collaboration networks for marine resource governance in both Kenya and Tanzania. Social proximity is the common driver of network formation. Collaboration networks in Kenya and Tanzania have contributed to enhanced learning among marine resource managers. Conclusions point to the need to focus on common challenges relating to low levels of rule-compliance, limited access to information on the state of resources and poor integration of science into marine management decisions. Finally, differences in views regarding the state of marine ecosystems need to be addressed to improve prospects for joint problem-solving in marine transboundary conservation.
Keywords: Adaptive co-management; Adaptive governance; Collaboration; Marine transboundary conservation; Social network analysis